On the work of Alexander of Tralles : O radu Aleksandra iz Trallesa - Panagiota, Kripouri (Array, 2019)
Helminthiasis is known to man since antiquity, but it still remains a significant public health problem. In ancient times many plants have been tried as possible therapeutics in search of an effective drug. This manuscript investigates ancient beliefs on parasitic worm infestation. Moreover, Alexander of Tralles’ (525 – 605 CE) suggestions on the treatment of this condition are discussed as found in his lesser-known work “A letter on helminths”, along with comments on the use of those herbal cures by modern medicine.